Unusual heavy rainfall during January to March 1984 Over Peninsular Inida (MAUSAM, 1988)
The rainfall associated with the retreating phase of the summer monsoon (popularly known as northeast monsoon), generally ends by the end of December over the Peninsular India. normally, rainfall during January to march is insignificant over this part of the country. However, in 1984, the rainfall during January to March was in exceptionally large excess from the normal In some of the meteorological sub-divisions in Peninsular India like Tamilnadu & Pondicherry, Kerala and coastal Karnataka. In this paper, an attempt has been made to investigate the synoptic situations leading to this excess rainfall.